2019
DOI: 10.3390/su11071967
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Financing for Sustainable Development: Agent-Based Modeling of Alternative Financing Models for Clean Energy Investments

Abstract: Renewable energy investments require a substantial amount of capital to provide affordable and accessible energy for everyone in the world, and finding the required capital is one of the greatest challenges faced by governments and private entities. In a macroeconomic perspective, national budget deficits and inadequate policy designs hinder public and private investments in renewable projects. These problems lead governments to borrow a considerable amount of money for sustainable development, although such e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Are these interventions worth the additional time, implementation, and reporting in order to meet global carbon targets? It is reported that financial institutions have stopped providing loans to unsustainable building projects [22,23]. The hesitancy might be understandable, as lenders may soon be required to report on how sustainable their loan portfolios are.…”
Section: Embodied Carbon and Current Strategiesmentioning
confidence: 99%
“…Are these interventions worth the additional time, implementation, and reporting in order to meet global carbon targets? It is reported that financial institutions have stopped providing loans to unsustainable building projects [22,23]. The hesitancy might be understandable, as lenders may soon be required to report on how sustainable their loan portfolios are.…”
Section: Embodied Carbon and Current Strategiesmentioning
confidence: 99%
“…The interconnection between the two concepts is that sustainable finance can contribute to strengthening economic resilience [23]. Responsible investment and proper management of risks associated with climate change and other environmental factors can enhance the economy's ability to cope with challenges and recover more quickly from shocks [24].…”
Section: Sustainable Financementioning
confidence: 99%
“…Banks advised to disclose a sustainability report according to a core or comprehensive selection; it can improve the quality of the sustainability report. [9] Clarke and Boersma's 2016 research recommends that sustainability performance is necessary for the critical performance indicators and senior executives' remuneration schemes. Regulatory reforms and changes to stock exchange listing rules can provide a framework for enhancing corporate directors' fiduciary duty towards environmental and social responsibility [10].…”
Section: Literature Reviewmentioning
confidence: 99%